FA’AALIYYAH ITQAAN FII TARJAMAH AN-NUSHUS AL-‘ARABIYYAH LILFASHL AT-TSAMIN (VIII A) FII AL-MADRASAH AT-TSANAWIYYAH “ANWARUL HIDAYAH” PAMIJAHAN BOGOR - Hendri; Muh Abrar; Usman (SHAWTUL ARAB, 2023)
Arabic is one of the foreign languages that many people have recently practiced to study and analyze, both of which are geared towards a standard and spiritual approach with the belief that Arabic is religious language because the Qur’an came down in Arabic as well. Through a comprehensive curriculum, who believes that Arabic is  a language worth studying in depth to learn about its historical and aesthetic studies. These problems will be analyzed so that they can be fixed and solutions will be found to overcome them in the future. This research is  a  qualititative research that uses data collection techniques in the form of observation, interviews and close interviews. The results showed: a ) Arabic teaches pumpkin skills to eighth-grade students in girls high school. The learning process begins with planning and implementation. The methods used by educators are lectures, vocabulary and evaluation. In the end, the educator provides motivation and evaluation to learn individual or group tasks,midterm exams, and final semester exams : b ). Learning problems for reading skills in case studies of archives include students : a ). Lack of interest in learning Arabic.b) lack of educational experience at the previous level of education. Students’ efforts to enjoy learning Arabic are by frequently opening dictionaries and studying the update